2020
DOI: 10.1002/jctb.6538
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and nutrient recovery of synthetic flowback water from shale gas extraction by air‐cathode (PMo/CB) microbial desalination cells

Abstract: BACKGROUND: Due to the rapid development of shale gas extraction, the treatment of flowback water (FW) is becoming one major challenge because of its high saline, high ammonium (NH 4 +), high phosphorus (PO 4 3−), and complex organic contents. This study aimed to treat the high-salinity synthetic FW and recover nutrient using the air-cathode (PMo/CB) microbial desalination cells (MDCs). RESULTS: The removal efficiency of chemical oxygen demand (COD) exceeded 90% along with an electricity generation of 105.6 mW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…2 the electrode and electrolyte slows due to the the ore from a high concentration of OBDCs, thereby leading to adverse effects on the conductivity of extracellular electrons. Additionally, a maximal current density of 2.66 A/m 2 was recorded at 2 g/L OBDCs, which was 1.6 times that of synthetic owback wastewater treatment in air cathode MFCs (under the same external resistance) as measured by Yang et al (Yang et al 2020a). This further demonstrated that the activity of electricity-producing microorganisms was the highest, and the oxidation decomposition rate of organic matter may have been the fastest at 2 g/L.…”
Section: Effect Of Sr On the Electricity Generation Performancesupporting
confidence: 66%
“…2 the electrode and electrolyte slows due to the the ore from a high concentration of OBDCs, thereby leading to adverse effects on the conductivity of extracellular electrons. Additionally, a maximal current density of 2.66 A/m 2 was recorded at 2 g/L OBDCs, which was 1.6 times that of synthetic owback wastewater treatment in air cathode MFCs (under the same external resistance) as measured by Yang et al (Yang et al 2020a). This further demonstrated that the activity of electricity-producing microorganisms was the highest, and the oxidation decomposition rate of organic matter may have been the fastest at 2 g/L.…”
Section: Effect Of Sr On the Electricity Generation Performancesupporting
confidence: 66%
“…Owing to the strong environmental adaptability and reproductive ability of Ascomycota, its relative abundance was an absolute advantage in each sample, which has also been reported in a variety of habitats, such as pioneer forests and tropical oligotrophic peatlands (Zhong et al, 2018;Morrison et al, 2021). At the family level, the bacterial community was mainly composed of Methlophagaceae, Desulfobulbaceae, Flavobacteriaceae, Nitrincolaceae, and Marinobacteraceae, which were widely distributed in many coastal wetland soils (Zhang et al, 2012;Risgaard-Petersen et al, 2015;Chen et al, 2020;Yang et al, 2021). Desufobulbaceae, regarded as 'cable bacteria' , was involved in the formation of a centimetre-deep suboxic zone in marine sediment through their role in the electrical couple of sulfide oxidation and oxygen reduction (Risgaard-Petersen et al, 2015).…”
Section: Responses Of Bacterial and Fungal Community Compositions To ...mentioning
confidence: 77%
“…At the family level, the bacterial community was mainly composed of Methlophagaceae, Desulfobulbaceae, Flavobacteriaceae, Nitrincolaceae, and Marinobacteraceae, which were widely distributed in many coastal wetland soils ( Zhang et al, 2012 ; Risgaard-Petersen et al, 2015 ; Chen et al, 2020 ; Yang et al, 2021 ). Desufobulbaceae, regarded as ‘cable bacteria’, was involved in the formation of a centimetre-deep suboxic zone in marine sediment through their role in the electrical couple of sulfide oxidation and oxygen reduction ( Risgaard-Petersen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…To gain a deeper insight on the rare portion of the gammaproteobacterial diversity, we conducted a higher-level taxonomic resolution analysis, which indicated that a total of eight gammaproteobacterial families were actually not rare locally (i.e., >1% contribution in at least one site), including Cycloclasticaceae, Halieaceae, KI89A clade, Nitrincolaceae, Rhodocyclaceae, Thioalkalispiraceae, Thiotrichaceae, and UBA10353 marine group ( Figure 4B ). All of these families include members recently reported to be particularly abundant in naturally-rich and/or contaminated environments that display high concentrations of HMs and/or hydrocarbons ( Gołębiewski et al, 2014 ; Singleton et al, 2015 ; Yang et al, 2016 , 2020 ; Suzuki et al, 2019 ; Bergo et al, 2020 ; Noirungsee et al, 2020 ; Sun et al, 2020 ). Notably, Cycloclasticaceae, Halieaceae, and Rhodocyclaceae, well known for their ability to degrade hydrocarbons, showed a peak in the site most contaminated by PAHs (S3; Figure 4B ; Table 1 ).…”
Section: Resultsmentioning
confidence: 99%